Land Classification Wadi Al-Salam Basin (Journal of the College of Education for Women, 2019)
Dry environment study forms an important part in the field of applies geomorphology forthe wide rang of its lands which form most of the world, homeland, and Iraqi lands specially,and what these lands include of scientific cases which needs to be searched and investigated.They include rocks, land shapes, water supplements, its ancient soil and its active diggings areall signs of the environment changes and effects that these lands under take over time, withcontinuous remains of its features of characteristics under geo morphological drycircumstances which works to slow change average, when the geomorphologic fearers variesin this environment and what it contain of important economical resource. As to participles inthis field the beast of wadi Al Salam was chosen as a subject of this research.